Correlation of Tooth Brushing Behavior and Consumption Patterns of Sugary Foods with Caries on Permanent Dentition at Twelve Years Children - Anak Agung Gede Agung; Ni Nyoman Dewi Supariani (Jurnal Kesehatan Gigi (Dental Health Journal), 2013)
Dental school health services is one way to increase the children awarness for maintaining oral health since early age which is expected to improve the oral health for all people but until now the incidence of dental caries is stilil high. Dental caries incidence in twelve years children still remains high is often associated with consumption patterhs of sugary food and not properly tooth brushing. This study aimed to determine the correlation of tooth brushing behavior and consumption patterns of sugary foods with caries on permanent dentition at twelve years children. This study is an observational with case control design used 144 of twelve years children as samples (72 cases and 72 controls). Case samples had been obtained based on examination by Health  School Services (UKS) of Puskesmas Densel IV mean while control samples were taken by a systematic random sampling. Data had been analyzed by univariate, bivariate with chi square, and multivariate with double regression. The results of the logistic regression test showed that the not properly tooth brushing can significantly increase the occuronce dental caries risk was 9.077 times. The consumption patterns of sugary foods can increase the occurance dental caries risk was 8.826 times. The not gargling habits with  water after eating sugary foods can increase dental caries risks was 3.250 times than the habitual of gargle with water after that. While variable of gender that no association with the incidence caries on permanent dentition at twelve years children. The tooth brushing behavior, consumption patterns of sugary foods, and gargling habits with water had related to incidence of dental caries. The gender were not related to the incidence of dental caries.